Pengaruh Customer Experience Quality Terhadap Customer Satisfaction & Customer Loyalty Di Kafe Excelso Tunjungan Plaza Surabaya: Perspektif B2C - Senjaya, Vivie (Jurnal Strategi Pemasaran, 2013)
This study discusses about the quality of the customer experience, which is thought to affect customer satisfaction at Cafe Excelso Tunjungan Plaza Surabaya. In this study, the variable of the customer experience quality is measured through the dimensions of accessibility, competence, customer recognition, helpfulness, personalization, problem solving, promise fulfillment, and value for time. Each of these dimensions will be partially tested how it affects customer satisfaction and customer loyalty. In addition, this study also wanted to know which the most influential dimension to customer satisfaction and customer loyalty are. The research sample was 200 visitors who visited the cafe Excelso Tunjungan Plaza Surabaya at least three times within a period of three months. The observations will be analyzed using the Covariance-Based Structural Equation Model (CB-SEM). The results from the study showed that the five dimensions of customer experience quality are accessibility, competence, helpfulness, personalization, and value for time, have a strong significant effect on customer satisfaction, but the dimensions of customer recognition and problem solving, only have a significant effect on customer satisfaction. On the other hand, the dimension of promise fulfillment has not given a significant influence. Other results showed that the eight dimensions of the quality of the customer experience has not been able to have a significant influence on customer loyalty, so it takes customer satisfaction as an intervening variable to achieve customer loyalty.